The role of Caixa Geral de Depósitos in the recent economic crisis (2007-2011): does public ownership make a difference? - Mortágua, Mariana Rodrigues (2012)
The public ownership of Caixa Geral de Depósitos (CGD), the biggest Portuguese commercial bank, has been a topic of controversy in the last 20 years. While public ownership is sometimes presented as both a source of competitive distortions in the banking industry and an instrument for the promotion of specific interest groups, its stabilizing role during the recent period of financial distress is hardly debatable. This dissertation intends to discuss the role of CGD as a State-owned bank in the context of the recent financial and economic crisis (2007-2011) by comparing its lending practices with the ones followed by private banks in Portugal. Evidence suggests that CGD played a counter cyclical role in the Portuguese economy by increasing its lending activity between 2007 and 2011, whereas all other private banks decreased their credit supply. Although Caixa might have benefited from special financing conditions from 2007 to 2009, after that moment the increase in Caixa‟s activity was mainly due to state capital injections. Therefore, the increase in CGD credit amounts during the period of crisis may reflect Caixa‟s political orientation towards other goals rather than profitability, such as the aggregate economic activity.